Contraception during Coronavirus-Covid 19 pandemia. Recommendations of the Board of the Italian Society of Contraception. (3rd May 2020) - Fruzzetti, F.; Cagnacci, A.; Primiero, F.; De Leo, V.; Bastianelli, C.; Bruni, V.; Caruso, S.; Di Carlo, C.; Farris, M.; Grandi, G.; Grasso, A.; Guida, M.; et al.
Abstract: Purpose: The Italian Society of Contraception identified as one of its priorities the need to give recommendations on management of contraception during Coronavirus-Covid 19 pandemia Materials and methods: A concise communication was produced which summarises in an easy-to-read format suitable for clinicians the management of the different contraceptives mostly used. Information how to manage contraception in different conditions is presented. Results: Women may, in general, continue to use either intrauterine and or hormonal contraceptives. The use of condom should be added to any hormonal contraceptive, when the contraceptive efficacy is reduced or when women stop the contraceptive method. Conclusion: At the present time, during the Coronavirus-Covid 19 pandemia, no data contraindicate the use of intrauterine or hormonal contraceptives. Conversely the use of an appropriate contraception is advocate to prevent unintended pregnancies.